Abundance and spatial patterning of coexisting perennial grasses in grazed shrublands of the Patagonian Monte - Pazos, Gustavo Enrique (2007)
We analysed the density, bunch size, and spatial patterning in relation to the shrubby matrix of the three dominant perennial grasses of the Patagonian Monte with different functional traits related to resource acquisition/conservation, mesophytism/xerophytism, and reproductive strategy. Field sampling was carried out at grazed (low and high grazing pressure) and excluded from grazing (15 years) sites. Grazing disturbance did not change the cover of the shrubby matrix but modified its spatial structure leading to increased density and reduced diameter of shrub patches. Changes in the abundance of perennial grass species among sites may be primarily attributed to a high direct effect of grazing on the species with the most mesophytic and acquisitive traits (N-rich green tissues, high leaf production, and low lignin concentration in leaves). Under grazing exclusion, this species was the most associated with shrub patches. The other perennial grass species either did not reduce or increased their abundance with grazing. The species with a mix of mesophytic and xerophytic traits was found with high frequency at inter-patch microsites. The most xerophytic and conservative species occupied vacant microsites either between shrub patches or at shrub-patch centres. However, the three species were increasingly concentrated under shrub canopies with increasing grazing pressure. This fact stresses the importance of shrub patches as biotic refuges for perennial grasses with low anti-herbivore defences.